Expert Consensus on Monitoring and Management of Patients with Critical Neurological Illness at High Altitudes - PHURBU Droma; CHEN Huan; CHEN Wenjin; DU Wei; LIN Guoying; PAN Wenjun; CHENG Li; GUI Xiying; CAI Xin; CHODRON Tenzin; FU Jianlei; LI Qianwei; et al. (Xiehe Yixue Zazhi, 2022)
Neurocritical care is an important branch of critical care medicine. The mechanism of critical neurological damage is complex and diverse, and the pathophysiology changes rapidly. Different pathophysiological changes determine different degrees of brain injury. In a special plateau environment, the incidence of critical neurological disease is higher, the age of onset is younger, the disease progress is faster, and the degree of damage is more severe. In order to standardize the diagnosis and treatment, enhance monitoring and management, provide timely and precise treatment, prevent irreversible brain injury, and improve the prognosis of patients with critical neurological illness at high altitudes, the Research Group of Calm Treatment of China, Research Group of Critical Care Ultrasound of China, and the Quality Control Center of Critical Care Medicine in Tibet formulated the Expert Consensus on Monitoring and Management of Patients with Critical Neurological Illness at High Altitudes on the basis of full discussion and communication of relevant critical medical experts and neurosurgery experts according to domestic and foreign literature and years of experience in clinical application and promotion. The main contents of the consensus are as follows.(1) According to the pathophysiological mechanism of neurological involvement in critical illness, scenarios of neurocritical care at high altitudes can be divided into cerebral hemorrhage at high altitudes, severe traumatic brain injuries, ischemic stroke, cerebral edema at high altitudes, and septic encephalopathy (8.4 points).(2) It is recommended to use cerebral blood flow, brain function monitoring and cerebral oxygen saturation as a 'triad' monitoring core in management of neurocritical care at high altitude, to as well as cerebrospinal fluid dynamics monitoring and brain structure surveillance (9.0 points).(3) It is recommended to grade patients quickly, and the '5-avoids' approach based on 'brain protection' theory were adhered to avoid fever, seizures, anxiety, agitation or pain, shivering, stimulation and nociception, according to different levels. Especially in the 'super critical' stage, with the protection of '446'targets, choose the window for analgesia and sedation (8.4 points).(4) It is recommended to monitor systemic and cerebral hemodynamic continuously and dynamically in order to improve systemic perfusion and optimize cerebral perfusion simultaneously (8.4 points).(5) It is recommended to choose the method of direct measurement of intracranial pressure by intraventricular catheter or optic nerve sheath diameter under ultrasound to estimate intracranial pressure, and choose the appropriate target mean arterial pressure to ensure optimal brain perfusion (8.8 points).(6) It is recommended to use transcranial Doppler ultrasound to evaluate the blood flow velocity and blood flow waveform of the bilateral cerebral arteries. It is recommended to target the blood flow velocity of M1 at 40 cm/s in the 'super critical' period (8.2 points).(7) In the 'super critical' period, we recommend to routinely monitor BIS and maintain the BIS value around 40 as the goal to guide the depth of sedation; those with conditions can be monitored by quantitative electroencephalography to assist determining whether there are non-convulsive seizures, and perform diagnostic evaluation of the prognosis (8.6 points).(8) It is recommended to monitor brain oxygen levels routinely, starting early in the ICU admission of patients with critical neurological conditions at high altitudes, which can assist in the assessment of brain damage (8.6 points).(9) It is recommended to evaluate the cerebral blood flow self-regulation ability routinely to achieve the optimal cerebral perfusion pressure in time and timely adjust the intensity and scheme of treatment (8.2 points).(10) It is recommended to emphasize the importance of target arterial partial pressure of carbon dioxide in the artery in critical illness and neurocritical care at high altitudes (8.0 points).(11) It is recommended to devote attention to the importance of targeted temperature management in in critical illness and neurocritical care at high altitudes (8.6 points).(12) It is recommended that multidisciplinary consultation and multi-professional cooperation could improve the management in critical neurological illness at high altitudes (8.8 points).(13) It is recommended that the constitution of improvement in brain structure imaging, pressure normalization of cerebrospinal fluid and restoration of cerebral blood autoregulation could be as the de-escalation triad (8.0 points).(14) It is recommended to be cautious of paroxysmal sympathetic hyperreactivity patients in neurocritical and critical illness at high altitude (8.0 points).(15) It is recommended to be cautious about the management of agitation (delirium) and cognitive function of patients in TBI at high altitudes(8.0 points).(16) It is recommended to assess the itinerary of the rehabilitation in a timely manner for critically sick patients at high altitudes (8.2 points).(17) It is recommended to be cautious of post-traumatic hydrocephalus and related neuroendocrine abnormalities in patients with critical neurological illness at high altitudes (7.6 points).